Prostitution of Indigenous Women: Sex Inequality and the Colonization of Canada’s First Nations Women (Fourth World Journal, 2005)
This article examines the impact of colonization on First Nations women in Canada, focusing on the systemic factors contributing to their vulnerability to prostitution. It explores how historical and ongoing colonial policies have created socio-economic conditions—such as poverty, marginalization, and violence—that disproportionately affect Indigenous women. The article highlights the intersectionality of race, gender, and class in shaping the lived experiences of these women, emphasizing how these overlapping systems of oppression contribute to their exploitation. By connecting prostitution with broader colonial structures, the article calls for urgent social and policy reforms to address these injustices and support the rights, dignity, and safety of Indigenous women in Canada.